A tragicomédia da modernidade: Shakespeare e Cervantes na Inglaterra do século XVII - Pajtak, Bruno Foschini (2018)
The objctive of this dissertation was to analyze the works of Shakespeare and Cervantes, specifically Troillus and Cressida (1602) and El Ingenioso Hidalgo Don Quixote de la Mancha (1605), noting that both were written in a context of great instability and paradigm changes both in Spain and England. The work of Cervantes will be analyzed here in the context in which it was published and read in Shakespeare's England, taking seventeenth-century London as the place of analysis. In order to do so, we will study the context in which the city became a major commercial and cultural center during the reign of Elizabeth I. We will also analyze the contexts of production and publication that involved the playwriters and the publisher-booksellers of the time who constantly fought for the monopoly of representation, always remembering that the concept of authorship was, at the time, in formation. Thus the research had to use the concept of representation formulated by New Cultural History to analyze disputes between court and city, between city and theater, between court and theater, and between book publishers and book authors , which lasted throughout the life of one of the greatest writers of all time, William Shakespeare